The Implementation of Rehabilitation Assessment As Legal Protection For Narcotics Abusers in Indonesia - Mikha Dewiyanti Putri; Prih Utami; Teddy Cipta Lesmana (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Nowadays, illicit trafficking and narcotics abuse have been at a dangerous level and threatened various aspects of the life of the nation and state and have even penetrated most levels of society, from the upper classes to the lower classes. The government reacted by issuing Law No. 35 of 2009 on narcotics as an amendment to Law No. 22 of 1997 on narcotics. Based on Article 4 letter d of Law 35 of 2009 concerning state narcotics, the government also provides legal protection for victims of narcotics abuse and addicts through medical rehabilitation and social rehabilitation. From Article 4 letter d of Law 35 of 2009 on narcotics, the researchers analyzed the process of rehabilitation assessments for victims of narcotics abuse and addicts. The researchers also analyzed and discussed the extent to which the laws and regulations in Indonesia have provided legal protection for them. The authors used library research methods that were juridical-normative. The research aimed to: 1) explain the rehabilitation assessment process for victims of narcotics abuse, the meaning of rehabilitation assessment, and the legal basis for rehabilitation assessment in Indonesian regulations; 2) explain the implementation of rehabilitation assessment for victims of narcotics abuse, including rehabilitation assessment related to the cases that researchers discussed in this article. Thus, this research answered several legal issues regarding rehabilitation assessment that exists and occurs in both theoretical and legal practice.Keywords: victims of narcotics abuse, rehabilitation assessment, legal protection.